Return to Drive Counseling After Sports-Related Concussion: A Quality Improvement Project - Stuart, Emily A. (Pediatr Qual Saf, 2016)
INTRODUCTION: Concussion is a common injury in adolescent athletes, many of whom also drive. Counseling athletes and their families about driving risks post concussion is a potentially significant intervention. The aim of this quality improvement project was to increase driving recommendations for concussed athletes in a pediatric sports medicine clinic. METHODS: Patients in this quality improvement project were seen in the sports medicine concussion clinic between February 2014 and August 2015. We determined how often driving recommendations were documented through a retrospective chart review. Once the “return to drive” project was introduced to the sports medicine staff, multiple interventions were completed including handing out flyers to remind families about driving and creating changes to the electronic medical record. RESULTS: At baseline, 9.3% of visits had driving recommendations documented. After an intervention requiring clinical documentation in the electronic medical record, 97% of patients received driving recommendations. CONCLUSIONS: The quality improvement effort was successful at increasing the frequency of delivery of appropriate driving recommendations provided to concussed athletes.